Experimental pain tolerance is associated with dental anxiety– the Tromsø study 2015–2016 - Hege Nermo; Natalia Petrenya; Ólöf Anna Steingrímsdóttir; Audun Stubhaug; Christopher Sivert Nielsen; Elin Hadler-Olsen (BMC Oral Health)
Abstract Background There are individual differences in pain sensitivity. Dental anxiety may increase the experience of pain during dental treatment, and painful dental treatments may trigger or amplify dental anxiety. This study aimed to explore if experimental pain tolerance in extremities, measured outside the setting of dental treatment, was associated with dental anxiety. Methods This cross-sectional study included participants from the seventh survey of the population based Tromsø Study with data on dental anxiety (n = 20 186, 40–99 years old, 52.4% women). Dental anxiety was assessed by the Modified Dental Anxiety Scale (MDAS). Tolerance to two experimental pain modalities was evaluated. Pressure pain tolerance (PPT) was measured by computerized cuff pressure on the leg as pressure endured up to a maximum of 100 kPa. Cold-pressor tolerance (CPT) was recorded as time to withdrawal of hand from circulating cold water to a maximum of 120 s. MDAS score across cohort characteristics was assessed with descriptive analyses. The association between pain tolerance and dental anxiety was assessed using binary negative binomial and multinomial logistic regressions adjusted for age, sex, personal finances, smoking, emotional distress, persistent pain, general-, and dental health. Results The median MDAS score was 6 (25-percentile: 5, 75-percentile: 9) and the mean was 7.7 (standard deviation: 3.8). Lower experimental pain tolerance was positively associated with MDAS score in fully adjusted models, with p-values for tests of linear trend < 0.001 for both PPT and CPT. Compared to not aborting the test, aborting PPT prior to 48.43 kPa and CPT before 25 s (cut-offs for the lowest tertile among those who aborted the tests) was associated with a 12% and 8% increase in MDAS score, respectively (p < 0.001). Multinomial logistic regressions showed that the association between experimental pain tolerance and MDAS scores was most pronounced in the highest MDAS category (≥ 19). Conclusions Although causality cannot be interpreted from this cross-sectional study, our findings suggests that a generalized low pain tolerance may render a person more vulnerable for development of dental anxiety. Dentists should have knowledge of and respect individual differences in pain tolerance and strive for optimal pain management in dental settings.